2017
DOI: 10.1109/jsen.2017.2748699
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Optical Fiber-Tip Cantilevers

Abstract: A microcantilever at the end face of an integrated optical fiber is reported, fabrication is uniquely achieved using a precision dicing saw. The methodology is a single-step rapid process, capable of achieving trenches with high aspect ratio (>10:1). The platform on which fabrication is made is a monolithic, integrated optical fiber. This integrally fuses optical fiber to a planar substrate using flame hydrolysis deposition (FHD) and high temperature consolidation (>1000 o C). This paper is the first report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Moreover, several other energy conversion processes could be utilized to actuate vibrations in a cantilever sensor, such as electromagnetic Lorentz forces [12,13]. On other hand, as sensing components, capacitive [14], piezoelectric [13], piezoresistive [15], and optical transducers [16] are the most commonly used methods in cantilever sensor applications. In this work, we develop MEMS-based cantilever sensors with embedded thermal excitation and piezoresistive sensing components.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several other energy conversion processes could be utilized to actuate vibrations in a cantilever sensor, such as electromagnetic Lorentz forces [12,13]. On other hand, as sensing components, capacitive [14], piezoelectric [13], piezoresistive [15], and optical transducers [16] are the most commonly used methods in cantilever sensor applications. In this work, we develop MEMS-based cantilever sensors with embedded thermal excitation and piezoresistive sensing components.…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies dealing with MEMS-based resonance sensors have indicated that they employ the thermal actuator due to its large actuation force [8], simple fabrication [9], and flexibility in the choice of materials [10]. Furthermore, piezoresistive-based sensing is also typically used in MEMS sensors besides capacitive [11], piezoelectric [12] or optical transducers [13]. Piezoresistors are the simplest form of piezoresistive devices with several advantages: low cost, small size, low phase lag, and extensive dynamic range [14].…”
Section: Introductionmentioning
confidence: 99%
“…FHD is a commercial technique used to deposit layers of doped silica onto the surface of a substrate for planar lightwave circuits and device integration [4,5]. The process is capable of depositing layers of silica soot several microns thick with levels of dopants tailored to suit a range of applications.…”
mentioning
confidence: 99%